Determinan pendapatan added worker pada wanita menikah - Widya Febriani; Yunisvita Yunisvita; M. Syirod Saleh (Department of Development Economics, Universitas Sriwijaya, 2016)
The loss work of the head family encourages other family members to enter the labor market to cover losses from the decline in family income referred to as the Added worker. This study aims to analyze the determinants of income added workers in married women. The data used in this study are secondary data for the year IFLS 5 (2014) obtained from the Indonesian Family Life Survey (IFLS). The analysis technique used in this study is multiple regression which is estimated by the Ordinary Least Square method. The results showed variable age of wife, and wife education had a positive and significant effect on income added workers in married women but not so because of the age of the husband. Whereas, the presence of 0-14 year old children and husband's education is not significant towards income added workers for married women.